ANALYSIS ON DESIGN APPROACH OF WHOLESALE KITCHEN MARKET IN DHAKA CITY - Tuli, Samina Mazumder; Islam, Nazmul (European Scientific Journal, ESJ, 2014)
Wholesale Kitchen Market is a vital function for a city due to its great contribution for providing food supply to city dwellers. Wholesale market is an essential component of any agricultural marketing system, especially for horticultural crops producing country like Bangladesh (Seidler, 2001). Dhaka, the capital city of Bangladesh, is one of the largest metropolitan cities of 565 square mile area with 14 million populations (City Population, 2011). Like any other megacity, Dhaka tries to meet its every day food demand from different edges of the country and even from abroad. Unfortunately, in Dhaka, wholesale kitchen markets are growing without having any particular planning guideline and operational system which results a completely unplanned, unorganized and unhygienic market system. Infact the overall scenerio of these masket places are highly crucial than imagination. Severe traffic congestion in the middle of the city due to unplanned loading and unloading system, inhuman working and living environment because of unorganized structural zoning system, intolerable pollution for unhygienic garbage disposal system are making the market place unapproachable. Considering a great demand, arising problems and sustainable solution; a design decision method will be proposed through this research for future development of Wholesale Kitchen Market in Dhaka city where the writting will focus on six major aspects of consideration and these are space requirements, zoning, transportation system and loading unloading, unit detail, human resource and waste management.